PROSEDUR PERMOHONAN KREDIT PADA KOPERASI UNIT DESA GAMPENGREJO II - Budiharto, Susetyo; Romaha, Nana (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2022)
The purpose of the cooperative is to advance the welfare of members in particular and society in general. This study aims to determine the credit application procedure in the cooperative. Is a type of descriptive qualitative research using secondary data from the Village Unit Cooperative (KUD) Gampengrejo II Village Paron District Gampengrejo Kediri regency.According to the results of character evaluation (character) there are 0.19% of the total applicant does not meet the criteria. The results of the evaluation of ability (capacity) there are 0.18% of prospective debtors meet the criteria. The results of the evaluation regarding capital (capital) are around 0.11% of prospective debtors do not meet the criteria. The results of the evaluation regarding collateral (collateral) are around 0.12% of prospective debtors do not meet the criteria. The results of the evaluation regarding conditions (condition) are 0.14% of prospective debtors do not meet the criteria. The procedure for granting credit starts from submitting a credit application to disbursing credit. The internal control system implemented in granting credit is quite good, the supervision applied in it has been carried out directly in order to avoid the possibility of fraud.